Radiosensitivity in callus tissues of soybean(glycine max.(L.)merril) - Alikamanoğlu, Sema; ATAK, ÇİMEN (My University, 1994)
Radiosensitivity of soybean as expressed by callus growth was examined after exposure of primary leaf explants with gamma rays.The leaf explants were irradiated 24 hours after incubation on the medium with gamma radiation doses of 0,5,7.5,10,25,50,75 and 100 Gy from Co-60 source. At the 30-day culture of callus the percentage of callus formation from irradiated explants was not different from the percentage of control callus formation. The decreasing average callus fresh weights were in connection with the increasing doses of the radiation and this relationship was significant (P<0.05).The differences between the doses of 5 Gy with 50 Gy and 100 Gy were significant (P<0.05) and the Gr-50 dose was found as 37 Gy for J-357 soybean variety.But the comparison of close doses of radiation was not significant from the point of decreasing average callus fresh weight
Keywords: RADIATION; THERMAL; AND OTHER ENVIRONMENTAL POLLUTANT EFFECTS ON LIVING ORGANISMS AND BIOLOGICAL MATERIALS; APPLIED LIFE SCIENCES; EXPERIMENTAL DATA; GAMMA RADIATION; MUTAGENS; RADIATION DOSES; RADIOSENSITIVITY; SOYBEANS; TISSUE CULTURES; DATA; ELECTROMAGNETIC RADIATION; FOOD; INFORMATION; IONIZING RADIATIONS; NUMERICAL DATA; RADIATIONS; SEEDS; VEGETABLES